Citizen identity formation of domestic students and Syrian refugee youth in Jordan: Centering student voice and Arab Islamic ontologies - Shephard, Daniel (JSSE - Journal of Social Science Education, 2024)
Patricia Kubow (2023). Citizen identity formation of domestic students and Syrian refugee youth in Jordan: Centering student voice and Arab Islamic ontologies. New York: Routledge. ISBN 9781003143215 https://doi.org/10.4324/9781003143215